(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this work, the Hyers-Ulam stability of first order linear difference operator TP defined by (Tpu)(n) = âˆ†u(n) - p(n)u(n); is studied on the Banach space X = lâˆž, where p(n) is a sequence of reals.